Cytomorphologic findings and differential diagnosis of pulmonary papillary adenoma: A case report and literature review. Issue 6 (4th April 2016) - Frey, Amy; Alatassi, Houda; Wiese, Tanya Ann; Fraig, Mostafa; Yang, Xiu
Abstract : Pulmonary papillary adenoma is a rare tumor of the lung. Some authors refer to it as papillary adenoma of type II pneumocytes. It demonstrates benign behavior, although some references suggest that this tumor may rarely exhibit invasive characteristics. We report a case of pulmonary papilloma adenoma of the lung diagnosed by fine‐needle aspiration biopsy and transbronchial biopsy. The patient is a 78‐year‐old woman, who presented to an outside facility with complaint of confusion after a missed episode of dialysis. On further workup, she was found to have a 3.8 cm irregular mass in the upper lobe of her right lung as visualized on chest CT. Fine‐needle aspiration and a concurrent forceps‐assisted transbronchial biopsy of the mass were performed. On microscopical examination, tumor cells formed small cohesive papillary fronds. On cytological evaluation, tumor cells were uniform medium‐sized epithelial cells with moderate cytoplasm, fine chromatin, and inconspicuous nucleoli. The biopsies showed papillary arrangement of epithelial cells in a background of mild fibrosis and chronic inflammation. There was no piling up of cells and the nuclei were uniform with bland appearance. No mitoses were appreciated, and Ki‐67 activity was low. The clinical decision was for observation. The patient suffered no complications after the procedures during 26 months of follow‐up. We hereby present this case with a review of the literature. Diagn. Cytopathol. 2016;44:543–547. © 2016 Wiley Periodicals, Inc.